2015
DOI: 10.1007/s11013-015-9470-7
|View full text |Cite
|
Sign up to set email alerts
|

A Doctor’s Testimony: Medical Neutrality and the Visibility of Palestinian Grievances in Jewish-Israeli Publics

Abstract: This paper follows the testimony of Izzeldin Abuelaish, a Palestinian physician who bears witness to his experiences working, living, and suffering under Israeli rule. He presents his story as a doctor's story, drawing on his identity as a medical professional to gain credibility and visibility and to challenge the limited legitimacy of Palestinian grievances. In this paper, I explore his testimony as a medical voice that at once recounts the suffering and loss endured by the Palestinian people and also strugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Trust is also crucial when understanding HCP’s intervention hesitancy in the context of ethnicity. While not a focus of study, previous research has identified the impact of ethnicity on the lived professional experiences of HCP in Israel, particularly among Israeli Arab HCP (Keshet et al 2015 , Shalev 2016 , Keshet and Popper-Giveon 2018 ). In Israel, low vaccination uptake is frequently found among minority populations (Rosen et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trust is also crucial when understanding HCP’s intervention hesitancy in the context of ethnicity. While not a focus of study, previous research has identified the impact of ethnicity on the lived professional experiences of HCP in Israel, particularly among Israeli Arab HCP (Keshet et al 2015 , Shalev 2016 , Keshet and Popper-Giveon 2018 ). In Israel, low vaccination uptake is frequently found among minority populations (Rosen et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Explanations of difference that use concepts of culture or behavior may work to manage ruptures in Arab–Jewish relations and to maintain the “political hygiene” [ 70 ] of the ED. However, we assert that in a city like Jerusalem where politics has an immense effect on patients’ lives, healthcare professionals should be cognizant of the socio-political structures that so many patients are unable to escape.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, during the decades‐long uprising in Indian‐controlled Kashmir, physicians worked for pro‐independence liberation organizations, treating victims of the violent uprising, and dealing with the fallout of a crumbling public health system (Varma 2020). Even when operating under the thin veneer of medical “neutrality” (Hamdy and Bayoumi 2016; Shalev 2016), physicians may find it difficult to evade political activation as they witness and respond to acts of state‐sanctioned violence.…”
Section: Physicians Agency and The Statementioning
confidence: 99%